MENTAL HEALTH PROBLEM IN INDONESIA IN PUBLIC STIGMA AND SELF-STIGMA PRACTICES - Dharwiyanto Putro, Bambang (International Conference on Cultural Studies; Vol 1 (2018): Proceedings International Conference on Cultural Studies, 2018)
In practice, the current legislation system has not adequately helped in improving mental health services. Stigma is still firmly attached to people with mental disorders that often become a victim of injustice and abuse by the public. A person with mental disorder is also commonly faced with stigma, discrimination and marginalization. The mental health Act is intended to ensure that everyone can achieve a good quality of life, enjoy a healthy psychiatric life as well as free from fear, pressure, and other disturbances that may interfere with mental health; ensure that everyone can develop the potential of intelligence; provide protection and guarantee services of mental health based on human rights; provide integrated, comprehensive and sustainable health services through promotive, preventive, curative and rehabilitative efforts; ensure the availability and affordability of resources in mental health efforts; improve the quality of mental health efforts in accordance with the development of science and technology; and provide an opportunity to be able to carry out its rights and obligations as an Indonesian citizen. Based on field facts as well as bibliographical studies conducted, the stigma forms in people with mental disorders remaining to occur indirectly become an evidence of the absence of the Law No.18/2014 on Mental Health that can be mentioned in two things, namely public stigma (stigma coming from society) and self-stigma (stigma coming from the sufferer and its own family). The forms of public stigma found in the research include rejection, exclusion and violence. Meanwhile, the forms of self-stigma consist of prejudices, feeling of guilty, fear and anger.